A COMPARISON OF THE PALATES OF PERMIAN AND TRIASSIC DICYNODONTS - Cruickshank, A. R. I. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1968)
Whilst comparing the skulls of some Triassic dicynodonts with Permian members of the family, it was noted that the interpterygoid space in the former is consistently smaller than in the latter (Cruickshank 1965: 1967). In analysing this difference further, the palates of a series of Permian and Triassic dicynodonts were examined, either directly or from published diagrams. From graphs drawn using the various measurements taken from the palates, the geological age of the specimens can be deduced as can their estimated lengths, if fragmentary.